Pencapaian Pembelajaran IPAS Siswa dengan menerapkan Forum Grup Diskusi Berdiferensiasi SDN 1 Agung Jaya - Fiolita Nurwulandari; Muhammad Ali Akbar (JUDIKA: Jurnal Pendidikan dan Bahasa, 2025)
The subject of Natural and Social Sciences (IPAS) in Grade V at SDN 1 Agung Jaya has shown suboptimal learning outcomes. This is due to the use of conventional teaching methods that are less interactive and do not consider individual student differences. This research aims to improve IPAS academic achievement through the implementation of the Focus Group Discussion (FGD) method facilitated by differentiated instruction. The study was conducted using the Classroom Action Research (CAR) model developed by Kemmis and McTaggart, carried out over two cycles. The participants consisted of 15 fifth-grade students. Several data collection techniques were used, including written tests, observation, interviews, and documentation. The written test was used to quantitatively measure learning outcomes, while interviews and documentation supported qualitative findings. The research results demonstrated a significant increase in student scores, with the average rising from 72 in the pre-cycle, to 79 in the first cycle, and 88 in the second cycle. The percentage of students meeting the Minimum Mastery Criteria (KKM) also improved, from 20%, to 60%, and finally to 87%. In addition to academic improvement, students showed enhanced active participation, collaboration, and critical thinking skills throughout the discussion process. Therefore, the integration of the FGD method with differentiated learning proved effective in improving both learning outcomes and student engagement. These findings are expected to serve as a practical reference for teachers in designing more inclusive and adaptive learning at the elementary school level.